ANALYSIS OF CATFISH FARMING BUSINESS DEVELOPMENT STRATEGY IN FISH FARM AGRIBUSINESS KARANG SARI VILLAGE SOUTH LAMPUNG - Novan Ardiansyah; Selfia Alkemega (ZILLZELL MEDIA PRIMA, 2024)
Indonesia is one of the countries that has abundant resources both from capture fisheries production and aquaculture fisheries. Catfish farming has profitable potential because the demand from the community is very high, while judging from the cultivation technique is relatively simple and quite easy. This research was conducted by analyzing how the catfish farming business development strategy in the Fish Farm Fisheries Agribusiness business of Karang Sari Village, South Lampung. The purpose of this study is to find out the catfish business development strategy in the Fish Farm Fisheries Agribusiness, this analysis method uses a qualitative analysis method using SWOT analysis in SWOT analysis divided into two groups, namely internal factors (IFAS) consisting of strengths and weaknesses and external factors (EFAS) consisting of opportunities and Threat. Based on the Internal Factor Analysis Summary (IFAS), the completeness score of all internal components (Quality and deficiency) is 3.13, while for the External Factor Analysis Summary (EFAS), it is known that from each external factor (Openings and Hazards) is 3.14. The results of the study of the SWOT analysis diagram produced are that the growth strategy is in quadrant 1, then the strategy applied is a growth strategy (Growth).